Research Progress on Terahertz Quantum-Well Photodetector and Its Application - Shao, Dixiang; Fu, Zhanglong; Tan, Zhiyong; Wang, Chang; Qiu, Fucheng; Gu, Liangliang; Wan, Wenjian; Cao, Juncheng (Frontiers in Physics, 2021)
Compared with other typical terahertz (THz) detectors, the quantum-well photodetector (QWP) has the advantages of high detection sensitivity, fast response, mature fabrication, small size, and easy integration. Therefore, it is suitable for high-speed detection and imaging applications at the THz band. Researchers, both domestic and overseas, have systematically studied material design and device performance of the THz QWP. The design of the device is such that the peak frequency error is within 8%, the maximum peak responsibility is 5.5 A/W, the fastest response speed is 6.2 GHz, the best noise equivalent power is ∼10−13 W/Hz0.5, and the spectrum range is 2.5–6.5 THz. In this article, firstly the basic principles and theoretical calculations of the THz QWP are described, and then the research progress of the THz QWP in our research group at imaging and communication is reviewed, which looks forward to its future development.